Factors Associated with Low Bone Mineral Density at the Time of Diagnosis in Children with Celiac Disease - Emine Çamtosun; Fatma İlknur Varol; Şükrü Güngör; Mukadder Ayşe Selimoğlu (Galenos Yayincilik, 2023)
INTRODUCTION: It has been reported that bone mineral density (BMD) is decreased in children with Celiac disease (CD) compared to their healthy peers. The aim of this study was to reveal possible risk factors for low BMD in Turkish children newly diagnosed with CD. METHODS: Eighty-six patients (2-18 years old) with CD were included in this retrospective study. The relationship between their lumbar BMD z-scores calculated according to their chronological age (CA) and height age (HA) and their clinical, laboratory [biochemical parameters, tissue transglutaminase antibody-IgA (TTGA) levels, human leukocyte antigen (HLA) types] and histopathological parameters were evaluated. RESULTS: The mean age of the patients at diagnosis was 8.06±4.08 years. The BMD z-score CA was ≤-2 standard deviation (SD) in 26.7% of the patients. The BMD z-score HA was ≤-2 SD in 12.8% of the patients. The BMD z-score HA only correlated with their age at diagnosis of CD (rs value 0.269). However, there was no statistically difference between the BMD z-score HA >-2 SD and ≤-2 SD subgroups regarding their clinical, laboratory and histopathological parameters. DISCUSSION AND CONCLUSION: Low BMD is common in children with newly diagnosed CD. Age at diagnosis, gender, body size, Celiac symptoms, biochemical parameters, TTGA level, HLA type, and histopathological stage had no predictive values in terms of low BMD in this patient group.